Asking the teachers: A Delphi study on the selection of skills and behaviours for an assessment of barriers to learning for pupils on the autism spectrum with intellectual disabilities. (29th October 2020) - Howell, Melanie; Bradshaw, Jill; Langdon, Peter E.
Accessible summary: Barriers make it hard for pupils to learn. We wanted to assess barriers to learning. We made an assessment called the Assessment of Barriers to Learning in Education‐Autism (ABLE‐Autism). We asked teachers to tell us about the barriers to learning. They told us about lots of barriers. We wanted to include the most important barriers. We used the Delphi method with teachers. The Delphi method helps people to agree what is important. Teachers told us about the most important barriers to learning. We included the most important barriers to learning in our assessment. Abstract: Background: This study outlines how a modified Delphi procedure was used with special educational needs teachers to select skills and behaviours for inclusion in the Assessment of Barriers to Learning in Education‐Autism (ABLE‐Autism). The ABLE‐Autism is a new teacher assessment to show progress in barriers to learning for pupils on the autism spectrum with coexisting intellectual disabilities in special schools. The research aim was to select items for inclusion in the assessment based on teacher ratings of relevance, comprehensibility and comprehensiveness. Method: Following a review of the literature and teacher focus groups, a list of 86 items was developed and a modified two‐round Delphi exercise was conducted with special needs teachers. Items were selected for inclusion if at least 80% of teachers agreed that the item was (a) able to be understood, (b) important to assess and (c) the median score associated with whether the item was able to be understood and important to assess was 1 (the highest score possible). Results: In the first round, 56 items met the criteria for inclusion and were retained. Thirty items were amended, and, after three items were amalgamated with other items, 27 amended items were included in the second round. After the second round, 14 additional items met the threshold to be included in the final assessment. Conclusions: After both rounds, 70 items were endorsed by teachers and included in the ABLE‐Autism. The input of special needs teachers provided initial face and content validity for the new outcome measure.